2021
DOI: 10.1155/2021/1954526
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Managerial Overconfidence, Cash Holding, and Investment Efficiency in Companies

Abstract: Managers’ overconfidence leads to overestimating their ability to manage cash sources. Holding more cash may result in overinvestment in projects and investment inefficiency consequently. The present study aims to investigate the effect of cash holding on investment efficiency with the moderating role of managerial overconfidence in Iranian companies. All listed firms in Tehran Stock Exchange, excluding banks, insurance, pension funds, and financial intermediaries, are included in the research. We have used da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Among the control variables in equation ( 2), Size and EPS have a positive effect on cash holdings; yet, leverage has a negative effect on cash holdings. The results of Asadia et al (2021) indicated a positive relationship between managerial overconfidence and cash holding. Overconfident managers are more likely to make challenging and risky investments than others (Chen et al, 2020).…”
Section: Data Analysis and Main Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Among the control variables in equation ( 2), Size and EPS have a positive effect on cash holdings; yet, leverage has a negative effect on cash holdings. The results of Asadia et al (2021) indicated a positive relationship between managerial overconfidence and cash holding. Overconfident managers are more likely to make challenging and risky investments than others (Chen et al, 2020).…”
Section: Data Analysis and Main Resultsmentioning
confidence: 89%
“…The Durbin-Watson statistics show that there is no serious autocorrelation in the error term. Based on the results of the Wooldridge test, there is autocorrelation in research model and the generalized least squares (GLS) test is used for estimating the coefficients of the model to deal with the issue and also the problem of variance heterogeneity Source: Research findings company value (Wei-Qiu, 2014), while the findings reported by Asadia et al (2021) showed that there is a significant negative relationship between cash holding and investment efficiency. However, managerial myopia has a significant negative effect on investment efficiency (sig < 0.05 and b = À0.014).…”
Section: Data Analysis and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations